Management of Fusarium Wilt of Castor (Ricinus communis L.) Caused by Fusarium oxysporum f.sp. Ricini with Biorationals and Fungicides under In vitro Conditions - , C. P. Manjula, C. Shijin Ravi, C. R Jahir Basha; Yamanura; Divyashree, J. Harish, Lakshmeesha R (Archives of Current Research International, 2024)
To mitigate the harmful effects of synthetic chemical pesticides, eight biorationals i.e ginger, onion, bougainvillea, garlic, chili, turmeric, neem, and aloe vera were tested at different test concentrations of 10%, 15%, and 20% against Fusarium oxysporum f. sp. ricini, the pathogen causing wilt in castor. Among all the tested biorationas, chilli found as most effective while aloe vera showed the least pathogen suppression. The study recommended neem and chili as effective biorationals against F. oxysporum f. sp. ricini. New fungicide combinations i.e Picoxystrobin + Tricyclazole, Fluopyram + Tebuconazole, Boscalid + Pyraclostrobin, and Iprovalicarb + Propineb were tested under in vitro condition out of which Picoxystrobin + Tricyclazole and the standard fungicides Carbendazim and Thiophanate-methyl showed cent percent inhibition at all tested concentrations (500, 1000, 1500 and 2000 ppm). Fluopyram + Tebuconazole and Boscalid + Pyraclostrobin also showed high efficacy, while Iprovalicarb + Propineb was the least effective. The study revealed that neem and chili are recommended as effective biorationals against F. oxysporum f. sp. ricini. Among fungicides, Picoxystrobin + Tricyclazole proved most effective, suggesting its potential for managing castor wilt.